Establishing Atrial Fibrillation Clinics: If not now, When? - Zair Hassan; Noohzad Gul; Usha Kumari (International Journal of Cardiology. Cardiovascular Risk and Prevention, 2021)
Background and objectives: Atrial Fibrillation (AFib) is the most common arrhythmia, associated with considerable morbidity and mortality. It affects 8% population and its incidence rises with age. The consequences of untreated or poorly treated Afib are grave, therefore, appropriate management of this condition should occupy high priority. Discussion: AFib clinic provides a prompt, well-organized, and conclusive approach to managing affected patients. The essence of such a set-up lays in providing frequent monitoring to the patient in well-equipped centres with specialized doctors and trained staff. Worldwide AFib clinics have shown evidence of morbidity, mortality, and cost-benefits. Conclusion: In developing countries such as Pakistan with less budget granted to health care, specialized AFib clinics could save cost, besides providing better health care outcomes to the patients. It is crucial to establish such focused AFib care centres urgently.